Nierenerkrankungen bei HIV‑Infektion - Bestandsaufnahme nach fast 40 Jahren Erfahrung mit HIV - Rieke, A.; Amann, Kerstin Ute; Lutz, J. (Nephrologe, 2020)
Human immunodeficiency virus (HIV) infections are nowadays a treatable chronic disease with a nearly normal life expectation. Kidney diseases play an increasingly important role in these patients due to the direct and indirect effects of HIV on the kidneys in the form of HIV-associated nephropathy (HIVAN), secondary glomerulonephritis, chronic inflammation and the increasing age with corresponding comorbidities. In patients with HIVAN and secondary glomerulonephritis an antiretroviral therapy (ART) should be quickly initiated; however, ART requires a continuous surveillance of the renal function as some medications can accumulate with decreasing renal function and can even have nephrotoxic effects themselves.
CRIS-Team Scopus Importer:2020-06-16
Keywords: AIDS-associated nephropathy; Antiretroviral therapy; Fanconi syndrome; Tubular transporters; Tubulopathy